Interleukin-33: A Mediator of Inflammation Targeting Hematopoietic Stem and Progenitor Cells and Their Progenies - Le, Hongnga; Kim, Wonyoung; Kim, Juyang; Cho, Hong R.; Kwon, Byungsuk (Frontiers in Immunology, 2013)
Inflammation is defined as a physiological response initiated by a variety of conditions that cause insult to the body, such as infection and tissue injury. Inflammation is triggered by specialized receptors in the innate immune system, which recognized by microbial components known as pathogen-associated molecular patterns (PAMPs) or endogenous signals produced by damaged cells (damage-associated molecular patterns, DAMPs). IL-33 is a cytokine that is released predominantly at the epithelial barrier when it is exposed to pathogens, allergens, or injury-inducing stimuli. IL-33 target cells are various, ranging from hematopoietic stem and progenitor cells (HSPCs) and essentially all types of their progeny to many nonhematopoietic cells. The pleiotrophic actions of IL-33 suggest that IL-33 is involved in every phase of the inflammatory process. In this review, we discuss recent advances in the understanding of how IL-33 orchestrates inflammatory responses by regulating HSPCs and innate immune cells.